Clinical Outcome of Non-descent Vaginal Hysterectomy Versus Abdominal Hysterectomy - Tiwari, Kenusha Devi; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Bharati, Sonu (Journal of Nepal Health Research Council, 2022)
Background: Hysterectomy is one of the most common operations performed by the gynecologists second to caesarean section. Hysterectomies are done vaginally, laparoscopically or abdominally. This study has been conducted to compare the complications of abdominal hysterectomy with non-descent vaginal hysterectomy with an aim to establish a safer, superior and lesser complication for the patients. Methods: This is a cross sectional study conducted at Kathmandu Model Hospital over the period of one year among 70 women. Women according to inclusion criteria were randomly allocated into two groups; 35 women in group 1 underwent non-descent vaginal hysterectomy and 35 in group 2 underwent total abdominal hysterectomy. Demographic data, intraoperative blood loss, intraoperative complications, operation time, postoperative complications, pain, and hospital stay was recorded and analyzed using statistical tool.. Results: The average age of the women was 45.77±6.33 years. Median blood loss (p=0.033) and hospital stay (p=0.005) was significantly low in group 1 as compare to group 2. Mean pain score at discharge (p=0.0005) and follow-up (p=0.0005) was also significantly less in group 1 as compared to group 2. Overall rate of complication was rare and not statistically significant between groups (p=0.643). Rate of wound infection was 5.7% that was observed in group 2, Vault infection 5.7% in group 1, UTI in 2 cases (5.7%) and paralytic ileus was found in 1 case in group 2. Conclusions: Non-descent vaginal hysterectomy is safe, effective and feasible procedure compared with abdominal hysterectomy. Less complications, faster operating time and easy recovery post operatively makes this a patient friendly mode of hysterectomy. Keywords: Hysterectomy; non-descent vaginal hysterectomy; vault infection; wound infection